Preparation and control mechanism of nano-phase change emulsion with high thermal conductivity and low supercooling for thermal energy storage. (November 2022) - Zhang, Guanhua; Guo, Yuqian; Zhang, Bin; Yan, Xiaoyu; Lu, Wei; Cui, Guomin; Du, Yanping
Abstract: In order to investigate the control mechanism of composite phase change materials (PCM), a series of composite nano-phase change emulsion (NPCE) were prepared in this paper with high thermal conductivity, high heat storage and low supercooling using hexadecane, octadecane, hexadecanol, octadecanol and various metal nano-particles. Through the control mechanism, it is expected to adjust the phase transition range of NPCE to a desirable range. The NPCEs were characterized by particle size analyser, cryogenic transmission electron microscope (Cryo TEM), differential scanning calorimeter (DSC), thermal conductivity meter and rheometer. The results showed that the NPCEs was successfully prepared with uniform dispersion, great stability, low viscosity and narrow particle size distribution. DSC results showed that the latent heat of NPCE with 20 wt. % hexadecane was 55.86 kJ/kg. The supercooling degree of prepared NPCEs using 1.25 wt. % of hybrid nucleating agents was reduced by 81%. Metal oxides effectively improved the thermal conductivity of NPCEs. The thermal conductivity of the NPCEs with 1wt. % nano Al2 O3 was 0.70 W/(m ⋅ K), which was increased by 21%. The viscosity of the NPCEs increased with the increase of metal oxide concentrations and decreased with the increase of temperature. Importantly the NPCEs presented a shear thinning effect and can be considered as Newtonian fluid after shear rate of 2 s −1, which had great potential in the thermal energy storage system. Highlights: Proposed control mechanism regulated the phase change to a desirable range. Addition of metal oxides improved the thermal conductivity of nano-emulsion by 21%. Supercooling was significantly reduced with metal oxides and hybrid nucleating agents. Prepared nano-emulsion can be considered as Newtonian fluid after shear rate of 2 s -1 .